Studi Etnobotani Pemanfaatan Tanaman Di Wilayah Adat Kampung Adat Cikondang Kabupaten Bandung Jawa Barat - Alfiah Rahmawati; Nur Ishaq Mahmudi; Tri Cahyanto (Lembaga Pengembangan Kinerja Dosen, 2023)
Ethnobotany has a very important role in society, including as a symbol of identity for a community group, including in the traditional area of ​​Cikondang Traditional Village, Bandung Regency, West Java Province. The traditional area is a small part of the traditional village covering an area of ​​3 hectares which consists of 7 sub-regions including prohibited forest, traditional rice fields, traditional gardens, traditional houses, traditional graves, saung lisung and bale paseban. The aim of this research is to examine the use of plants in traditional areas by the people of Cikondang Traditional Village in daily life, architecture and traditional ceremonies. This research is a qualitative research approach using survey methods and semi-structured interviews. 34 types of plants from 24 families were obtained, the highest use was as traditional ritual materials and the most widely used part of the plant was fruit. The people of Cikondang Traditional Village have a strong attachment to plants as evidenced by the use of plants in various aspects of their lives.